(untitled) (One Health & Risk Management, 2025)
Introduction. In the context of accelerated climate change and the rising frequency of heatwaves, patients with neurological disorders represent a high-risk group. Heat stress can adversely affect their health, necessitating appropriate adaptations in medical practice. This study aimed to develop and validate a KAP (Knowledge, Attitudes, Practices) questionnaire to assess neurologists’ perceptions and approaches regarding the impact of heat stress during heatwaves on patients with neurological disorders. Material and methods. The study included a literature review phase to establish the theoretical foundation, followed by a practical phase for questionnaire development, content validation through expert consultation, and pre-testing on a sample of 104 neurologists. The clarity and relevance of the items, as well as the instrument’s internal consistency, were evaluated (Cronbach’s alpha coefficient = 0,82). Results. An original 35-item questionnaire was developed and organized into three thematic sections. The pilot study confirmed the instrument’s clarity and applicability, and preliminary psychometric analysis demonstrated satisfactory internal consistency. Conclusions. The questionnaire is a valid tool, adapted to the climatic and professional context of the Republic of Moldova. Applying it to larger samples will enable more in-depth psychometric analysis and support the development of adaptive medical strategies for addressing heat stress.